Sorting on the Used-Car Market After the Volkswagen Emission Scandal - Anthony Strittmatter; Michael Lechner (Center for Economic Studies and ifo Institute (CESifo), 2017)
The disclosure of the VW emission manipulation scandal caused a quasi-experimental market shock in the observable quality of VW diesel vehicles. We consider a classical model for adverse selection and sorting to derive an empirically testable hypothesis about the impact of observable quality on the supply of used cars. We test the hypothesis with data collected from an online car selling platform which reflects about 50% of the German used-car market. The empirical approach is based on a conditional difference-in-differences method. We find that the supply of used VW diesel vehicles increases after the VW emission scandal. This finding is consistent with the predictions of the theoretical model. Furthermore, we find the positive supply effects increase with the probability of manipulation.
Keywords: D82; L15; L62; 330; supply of used cars; quality of durable goods; sorting; difference-in-differences; management fraud